Autonomy Practiced by English Primary School Teachers to Develop Teaching Professionalism - Felayabi, Hasbie; Purnawarman, Pupung; Sukyadi, Didi (Mimbar Sekolah Dasar, 2022)
Teachers’ autonomy allows teachers to be in charge of their teaching, from preparing syllabuses, teaching materials, and evaluation. For elementary school teachers, this autonomy is essential since this level of education is fundamental to the lifelong learning process. Teachers’ autonomy can also be a form of professional action that leads to professional development. Hence, this study aims at identifying teachers’ perceptions about teachers’ autonomy, finding out what they have implemented in promoting teachers’ autonomy, and acknowledging their awareness of the importance of teachers’ autonomy. This study employed qualitative research and case studies as its framework. Online questionnaires were distributed to elementary school teachers of public and private schools, and interviews were conducted to follow up on the answers obtained from the questionnaires. The results suggest that teachers’ autonomy was driven by the teachers’ needs for personal and professional development. It was also revealed that the participants had practiced the five dimensions of autonomy-supportive practices, namely organizational and procedural autonomy, rationale and relevance, responsiveness, feedback, and cognitive autonomy support. Additionally, they also believe that the practice of teachers’ autonomy will be optimal with the support of the managerial system, be it the school, the stakeholders, or the government.